Case Study of Reducing Pain Scale in Patients Benign Prostate Hyperplasia Post TURP Uses The Murrotal Distraction Relaxation Technique - Rizky Meuthia Pratiwi; Ayu Wastiti Eka Monitha (Kirana Publisher (KNPub), 2023)
Introduction : Benign prostatic hyperplasia is a diagnosis that refers to the proliferation of epithelial tissue and smooth muscle in the prostatic transition zone (Reynardi 2021). One of the actions taken to overcome the problem of BPH is TURP (Transuretharl Resection Of the Prostate). Methods: This study used the case study method with 1 patient and 1 case of nursing problems in postoperative TURP patients who experienced acute pain problems. Results: After nursing interventions with relaxation techniques and distraction techniques in Postoperative TURP patients showed that distraction relaxation techniques can reduce pain levels in patients from scale 5 to scale 2 and also the criteria for the results achieved Conclusion: Distraction Relaxation Techniques with Murrotal can reduce pain scale in postoperative patients.